Comparison Analysis between Kinect Grayscale and Depth Images - Antoni, Fajria; Asyhab, Naufal; Yazid, Ahmad Subhan; Rifa'i, Aulia Faqih (IJID (International Journal on Informatics for Development), 2016)
The purpose of this research is to know which method is more appropriate in the application of user interfaces. A data collection method used in this research is the literature study. This literature study method is done by reading books, scientific journals, papers, and using internet media as a source of information. Based on the research conducted it can be concluded that from both methods it has advantages and disadvantages. Grayscale method is good for fast processing and image processing. While the depth method is good for applications that require a high level of accuracy and require high resources.